Event Tourism of the Middle Dnieper Region as a Strategic Direction of Regional Development - Соколовський, Віктор Анатолійович; Щоголєва, Інна Валентинівна (Київський національний університет імені Тараса Шевченка, 2020)
The purpose of the article is to substantiate the role of event tourism as a strategic direction for the development of the Middle Dnieper region. Methodology. The tourism industry is sensitive to the effects of both external and internal factors, therefore, determining the strategic directions of development and predicting their state causes certain difficulties. However, the absence of a defined development vector excludes the activation of the resources, the use of which would make obtaining positive economic and social effect possible. The study information base is the websites of the Kirovograd and Cherkassy regions state administrations as well as the Strategy for their development until 2027. Analytical, comparative and historical research methods were used to solve the main tasks. Results. The features of the historical development of event tourism have been considered and the factors of its popularization have been analyzed. General analysis of the regional event resources has been made. Based on the tourist region evolution model by R. Butler, the spatial tourism model by Tuner-Weber and the geomarketing approach, the strategic importance of the event tourism development in the territory of the Middle Dnieper region has been substantiated. The events held in the territory of the Middle Dnieper region have been systematized. Based on the events analysis within the region, it was determined that the most common direction is festivals of various scales, ranks and themes. The development priority of event tourism in the context of Development strategies of the Kirovograd and Cherkasy regions for 2021-2027 has been proved. Scientific novelty. The spatial-territorial structure of event tourism in the Middle Dnieper region has been analyzed. Events in the territory of the Middle Dnieper region have been systematized according to various criteria. Comprehensive research of festival events as the most promising direction of event tourism in the Middle Dnieper region has been made. Practical significance. The conducted research can be considered a basis for further research of the tourist potential of the Middle Dnieper region, in particular, its event resources. The research results can be used in planning of tourist activities in the Middle Dnieper region, providing for monitoring and subsequent analysis of the necessary material and technical base; natural, natural-anthropogenic and socio-historical tourist resources; human resources involved in tourism, in particular, their quantitative and qualitative representation; the most popular activities, events having a strong development potential. Realization of the event potential of the Middle Dnieper region will have an impact on the formation of the regional tourism policy and commitment of local business figures in their consolidation about the events, in the process of creating various cluster associations, especially of tourism destination, and contribute to fund-raising.

Мета дослідження ‒ обґрунтування ролі івент туризму як стратегічного напряму розвитку Середнього Придніпров’я. Методика. Індустрія туризму є чутливою до впливів як зовнішніх, так і внутрішніх чинників, тому визначення стратегічних напрямків розвитку та прогнозування їх стану викликають певні труднощі. Але відсутність заданого вектору розвитку унеможливлює активізацію ресурсів, використання яких дало б позитивний економічний і соціальний ефект. Інформаційною базою дослідження є сайти державних адміністрацій Кіровоградської та Черкаської областей, а також Стратегії їх розвитку до 2027 року. Для вирішення основних завдань дослідження використано аналітичний, порівняльний та історичний методи дослідження. Результати. Розглянуто особливості історичного розвитку івент туризму та проаналізовано чинники його популяризації. Здійснено загальний аналіз подієвих ресурсів регіону. Обґрунтовано стратегічну важливість розвитку івент туризму на території Середнього Придніпров’я на основі моделі еволюції туристичного регіону Р. Батлера, просторової моделі туризму Тюнера-Вебера та геомаркетингового підходу. Систематизовано івенти, які проводяться на території Середнього Придніпров’я. На підставі аналізу івентів в межах регіону визначено, що найбільш поширений напрям – фестивалі різного масштабу, рангу та тематики. Доведено пріоритетність розвитку івентивного туризму в контексті Стратегій розвитку Кіровоградської та Черкаської областей на 2021-2027 рр. Наукова новизна. Проаналізовано просторово-територіальну структуру івент туризму в Середньому Придніпров’ї. Систематизовано івенти на території Середнього Придніпров’я за різними критеріями. Здійснено комплексне дослідження фестивальних заходів як найбільш перспективного напрямку івент туризму в Середньому Придніпров’ї. Практична значимість. Проведене дослідження може розглядатись як основа для подальшого дослідження туристського потенціалу Середнього Придніпров’я, зокрема, його подієвих ресурсів. Результати дослідження можуть бути використані при плануванні туристської діяльності в Середньому Придніпров’ї, яке передбачає моніторинг та подальший аналіз стану необхідної матеріально-технічної бази; природних, природно-антропогенних та суспільно-історичних туристських ресурсів; людських ресурсів, задіяних у сфері туризму, зокрема, їх кількісного та якісного складу; найбільш популярних подієвих заходів, івентів, які мають потужний потенціал для розвитку. Реалізація подієвого потенціалу Середнього Придніпров’я буде мати вплив на формування регіональної туристської політики та зацікавлення місцевих бізнес-кіл в консолідації навколо івентів при створенні кластерних об’єднань різного, особливо туристичного, спрямування, а також сприяти залученню інвестицій.
Івент-туризм Середнього Придніпров’я як стратегічний напрям регіонального розвитку
Keywords: івент туризм; туристські ресурси; подієві ресурси; фестивалі; просторово територіальна структура; регіональний розвиток; стратегії розвитку; Середнє Придніпров’я; event tourism; tourist resources; event resources; festivals; spatial and territorial structure; regional development; development strategies; the Middle Dnieper region